Raspberry Pi computer vision programming : design and implement computer vision applications with Raspberry Pi, OpenCV, and Python 3.x /: design and implement computer vision applications with Raspberry Pi, OpenCV, and Python 3.x. (2020) - Pajankar, Ashwin
No abstract available